The impact of city block type on residential burglary: Mexico City as case study - Vilalta, Carlos J. (Crime, law and social change, 2021)
Using block level data for Mexico City as case study, this article provides evidence that the type of city block type correlates with the likelihood of residential burglary. We employed five multilevel random intercept models to relate burglary incidents to city block types. We nested the 64,282 city blocks of Mexico City within their corresponding 846 local police quadrants. Our results show that Container-type city block configurations are associated with residential burglary to a greater degree than other physical and social environmental variables. Also, we find that close proximity to mass transit locations is not associated with residential burglary activity. The overall findings of this study describe fundamental dynamics between urban form and burglary.